2019
DOI: 10.1002/glia.23742
|View full text |Cite
|
Sign up to set email alerts
|

Liver kinase B1 depletion from astrocytes worsens disease in a mouse model of multiple sclerosis

Abstract: Liver kinase B1 (LKB1) is a ubiquitously expressed kinase involved in the regulation of cell metabolism, growth, and inflammatory activation. We previously reported that a single nucleotide polymorphism in the gene encoding LKB1 is a risk factor for multiple sclerosis (MS). Since astrocyte activation and metabolic function have important roles in regulating neuroinflammation and neuropathology, we examined the serine/threonine kinase LKB1 in astrocytes in a chronic experimental autoimmune encephalomyelitis mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 92 publications
(99 reference statements)
0
5
0
Order By: Relevance
“…We next investigated the mechanisms linking bilirubin production and ERRα upregulation in KRGE-treated astrocytes. A recent report demonstrated that LKB1-deficient astrocytes exhibit impaired metabolic function and enhanced inflammatory activation [ 18 ]. Interestingly, bilirubin increased LKB1 phosphorylation in a concentration-dependent manner ( Figure 3 b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next investigated the mechanisms linking bilirubin production and ERRα upregulation in KRGE-treated astrocytes. A recent report demonstrated that LKB1-deficient astrocytes exhibit impaired metabolic function and enhanced inflammatory activation [ 18 ]. Interestingly, bilirubin increased LKB1 phosphorylation in a concentration-dependent manner ( Figure 3 b).…”
Section: Resultsmentioning
confidence: 99%
“…The energy metabolism kinase LKB1 helps maintain ATP levels and is critical for neuronal survival following mitochondrial dysfunction [ 19 ]. LKB1-deficient astrocytes exhibit impaired metabolic function and enhanced inflammatory activation [ 18 ]. Under physiological circumstances, KRGE activates the LKB1–SIRT1–ERRα pathway, thereby stimulating Tom20/Tom22 complex-mediated SIRT5 expression.…”
Section: Discussionmentioning
confidence: 99%
“…It is crucial to determine if LKB1 signaling controls the metabolism and function of oligodendrocytes and OPCs, and if LKB1 deficiency causes mitochondrial dysfunction and progressive axon degeneration of CNS neurons. LKB1 deficiency in astrocytes has been reported to reduce astrocytic metabolic function and enhance inflammatory responses [ 95 ]. The LKB1-AMPK signaling pathway may also modulate the actions of microglia under certain conditions [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite being neither immune progenitors nor strictly classified as innate immune cells, astrocytes can perceive inflammatory signals and regulate neuroinflammation. Some studies have suggested a possible connection between abnormal gene expression in astrocytes or metabolic abnormalities and increased neuroinflammation (223)(224)(225). Wheeler et al (226) utilized single-cell RNA sequencing combined with cell-specific Ribotag RNA profiling, assay for transposase-accessible chromatin with sequencing, chromatin immunoprecipitation with sequencing, genome-wide analysis of DNA methylation and in vivo CRISPR-Cas9-based genetic perturbations to examine astrocytes in MS and EAE.…”
Section: Astrocytesmentioning
confidence: 99%